OPTIMIZATION OF PERSONALIZED SELECTION OF SINGLE EMBRYOS IN ASSISTED REPRODUCTIVE TECHNOLOGY PROGRAMS USING MOLECULAR GENETIC TECHNOLOGIES (The New Uzbekistan Journal of Medicine, 2025)
The current development of assisted reproductive technologies (ART) is aimed at increasing the effectiveness of in vitro fertilization (IVF) programs while minimizing obstetric and perinatal complications. One of the key areas is the optimization of personalized selection of single embryos (Single Embryo Transfer, SET). The traditional practice of transferring two or more embryos increases the likelihood of pregnancy but is associated with a high risk of multiple pregnancies. The use of molecular genetic technologies, including preimplantation genetic testing (PGT), transcriptomic analysis, and epigenetic markers, significantly improves the accuracy of embryo selection. This article analyzes modern approaches to personalized SET, including the integration of morphokinetic assessment, genetic diagnostics, and endometrial receptivity assessment. Prospects for implementing new technologies to achieve an optimal balance between the safety and effectiveness of ART are discussed.